Effect of Organic Manure and Mineral Fertilizers on Bioaccumulation and Translocation of Trace Metals in Maize - Wajid, Kinza; Ahmad, Kafeel; Khan, Zafar Iqbal; Nadeem, Muhammad; Bashir, Humayun; Chen, Fu; Ugulu, Ilker (Bulletin of environmental contamination and toxicology, 2020)
Mineral fertilizers and organic manure are used as soil amender to enhance the mineral status of the soil. These fertilizers contain trace metals besides providing macro and micronutrients. The present study was performed to observe the effect of mineral fertilizers, poultry manure and cow manure on trace metal content of soil and various parts (root, shoot, and grains) of maize plant ( Zea mays L.). The analysis of metals was performed by atomic absorption spectrophotometer (AA-6300 Shimadzu Japan). The highest level of Pb, Fe, Ni and Cu was observed in the root as 0.36–0.55, 70.41–83.03, 4.98–7.44 and 2.94–4.43 mg kg − 1 , respectively. The highest level of Cd, Zn and Mn was determined in grains as 0.44–1.59, 28.05–46.39 and 26.24–46.57 mg kg − 1 , respectively. The values of all metals were found within their permissible limit given by FAO/WHO except for the Cd. The interactive use of mineral and organic fertilizers enhanced the level of trace metals in maize as compared to their sole application. In the present findings, the health risk index for all metals was less than 1 in all treatments. So, it was concluded that the level of metals in poultry manure, cow manure and mineral fertilizer treated maize did not pose any potential threat to the consumers.